Risk factors for glioblastoma therapy associated complications - Ening, Genevieve; Capper, David; Schmieder, Kirsten; Brenke, Christopher (Clinical neurology and neurosurgery, 2015)
Objective Thromboembolic events, seizures, neurologic symptoms and adverse effects from corticosteroids and chemotherapies are frequent clinical complications seen in Glioblastoma (GB) patients. The exact impact these have on dismal patient outcome has not been fully elucidated. We aimed at assessing treatment associated complications, evaluating the impact on survival and defining risk factors. Methods Two hundred and thirty three consecutive adult patients operated on for newly diagnosed GB at a single tertiary institution over a 5-year-period (2006-2011) were assessed. Demographic parameters (age, gender, comorbidity status quantified by the Charlson-comorbidity-index (CCI), functional status computed by the Karnofsky Performance Scale (KPS), tumor characteristics (size, location, IDH-1 mutation and MGMT-Promotor-methylation-status) and treatment parameters (volumetrically quantified extent of resection and adjuvant therapy) were retrospectively reviewed. Complications assessed were recorded as neurological (N), surgical (S) and medical (M). Independent risk factor analysis was performed by the univariate and multivariate logistic regression method. Survival analysis was plotted by the Kaplan-Meier-method, influence of complication occurrence was evaluated by the log-rank test. Results One hundred and fifty nine (68.2%) patients had a total of 281 complications (90 N, 174 M and 17 S). Univariate analysis identified age (P = 0.003), KPS < 70 (P = 0.002), CCI > 3 (P = 0.03), eloquent tumor location (P = 0.001) and therapy other than the standard radio-chemotherapy with temozolomide therapy (P = 0.034) as risk factors for complications. Multivariate analysis extracted the eloquent tumor location (P = 0.007, odds ratio 1.94) as a significant predictor for complications. Having a complication significantly decreased patient survival (P = 0.015). Conclusions Complications significantly decrease GB patient survival. Age, poor functional status, other than standard adjuvant therapy and eloquent tumor location proved as significant risk factors for encountering a therapy associated complication. Not extensive surgery or tumor size but surgery at eloquent locations impacts complication occurrence the strongest with a 2 fold increased complication occurrence risk.